How The Implications of Assessment for Guidance and Counseling in Schools? - Rima Pratiwi Fadli; Daharnis Daharnis; A Muri Yusuf (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Assessment in counseling and guidance activities typically takes the form of outcome and process evaluation. The effectiveness of counseling services as viewed from the process is assessed through process evaluation. An evaluation of the outcomes is used to gather data on the efficiency of counseling and guidance services. An essential part of managing a mentoring program is assessment. Without an assessment, it would be impossible for us to determine whether the intended guidance program had been implemented successfully. The evaluation of the guidance program is to determine the degree to which the program's implementation has met its stated objectives. In other words, the outcome of the assessment activities will determine whether the program is successful in reaching its objectives.